2022
DOI: 10.3746/pnf.2022.27.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red Rice Bran Extract on High-Fat Diet-Induced Obesity and Insulin Resistance in Mice

Abstract: Insulin resistance is a salient player in the pathogenesis of obesity and its related abnormal glucose-insulin homeostasis. Red rice bran extract (RRBE) demonstrates several bioactive phytochemicals with anti-diabetic properties. However, little is known about its molecular mechanisms. Therefore, the present study was designed to investigate the anti-insulin resistant mechanisms of RRBE in a model of high-fat diet (HFD)-induced insulin resistance. In this study, mice were randomly divided into four groups: low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…HRV and BP variables did not change after either form of supplementation, and no differences were found between the groups. Supplementation with rice bran and its active components, such as oryzanols, tocopherols, tocotrienols, phytosterols, and nucleotides, has been shown in animal experiments to be effective against chronic diseases such as hypertension, dyslipidemia, diabetes mellitus, metabolic syndrome, obesity, and inflammation (Ardiansyah et al, 2009;Palou et al, 2015;Wang et al, 2015;Alauddin et al, 2016;Duansak et al, 2022;Munkong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…HRV and BP variables did not change after either form of supplementation, and no differences were found between the groups. Supplementation with rice bran and its active components, such as oryzanols, tocopherols, tocotrienols, phytosterols, and nucleotides, has been shown in animal experiments to be effective against chronic diseases such as hypertension, dyslipidemia, diabetes mellitus, metabolic syndrome, obesity, and inflammation (Ardiansyah et al, 2009;Palou et al, 2015;Wang et al, 2015;Alauddin et al, 2016;Duansak et al, 2022;Munkong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated a potential role of obesity-induced inflammation in the development of insulin resistance ( Uysal et al, 1997 ; Kamei et al, 2006 ; Saberi et al, 2009 ; Pierre et al, 2013 ). Prolonged ingestion of HFD (8∼16 months, 40∼60% energy from fat) in C57BL/6J mice leads to hyperglycemia, hyperinsulinemia, and impaired insulin sensitivity in addition to a significant rise in bodyweight, fat mass, and inflammation ( Do et al, 2011 ; Avtanski et al, 2019 ; Munkong et al, 2022 ). van der Heijden et al (2015) have implied that obesity-associated insulin resistance is possibly more linked to inflammation in adipose tissue rather than other tissues such as the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, RRBE supplementation improved the serum insulin level, glucose level, and expression of insulin-degrading enzyme (IDE), insulin receptor substrate (IRS), and glucose transporter (GLUT) in high-fat-diet-induced obese mice. RRBE protects the host from diet-induced damage by improving glucose–insulin homeostasis [ 98 ].…”
Section: Anti-obesity Properties Of Rice Branmentioning
confidence: 99%